2016
DOI: 10.5351/kjas.2016.29.1.013
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of high speed train on the regional economy of Korea

Abstract: High-speed railway (Korea Train Express) has had a deep impact on the regional economy of Korea. Current high-speed rail research is mostly theoretical, there is a lack of quantitative research using a precise algorithm to study the effect of high-speed railway on the regional economy. This paper analyses the influence of highspeed rail on the regional economy, with a focus on the Daegu area. Quantitative analysis using department store indexes and regional medical records is performed to calculate the economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…They concluded that there is no negative impact of KTX on the local shopping activities at least in the first year of its introduction, although the respondents in local areas expected more visitors from the Seoul metropolitan area rather than those from local cities because of the reduced travel times. Park and Kim [19] investigated the effect of Gyeongbu KTX on the regional economy. They focused on the department store and regional medical records to calculate the economic influence of the KTX.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that there is no negative impact of KTX on the local shopping activities at least in the first year of its introduction, although the respondents in local areas expected more visitors from the Seoul metropolitan area rather than those from local cities because of the reduced travel times. Park and Kim [19] investigated the effect of Gyeongbu KTX on the regional economy. They focused on the department store and regional medical records to calculate the economic influence of the KTX.…”
Section: Literature Reviewmentioning
confidence: 99%